Counting the Cost : A Memoir - Duggar, Jill; Dillard, Derick; Borlase, Craig (New York : Gallery Books, 2023)
"For the first time, discover the unedited truth about the Duggars, the traditional Christian family that captivated the nation on TLC's hit show 19 Kids and Counting. Jill Duggar and her husband Derick are finally ready to share their story, revealing the secrets, manipulation, and intimidation behind the show that remained hidden from their fans"--
Keywords: Duggar, Jill; Dillard, Derick; 19 kids and counting (Television program); Television personalities -- Biography. -- United States; Ex-cultists -- Biography. -- United States; Reality television programs -- United States; Families; Family secrets; Christian life; Autobiographies